Proceedings of the VII European Congress on Computational Methods in Applied Sciences and Engineering (ECCOMAS Congress 2016) 2016
DOI: 10.7712/100016.2155.5285
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Collapse Fragility Models of Rc Framed Buildings Based on Pushdown Analysis

Abstract: Abstract. Partial or total progressive collapse under abnormal loading conditions (e.g. deliberate terrorist attacks, uncontrolled gas releases, and vehicle or aircraft impacts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…In previous studies [85][86][87][88], considerations were also given for study of entire frame system of a buildings and bridge structures under synergetic effects of combined blastimpact loads resulting partial or total progressive collapse.…”
Section: Response Of Structures Under Blastmentioning
confidence: 99%
“…In previous studies [85][86][87][88], considerations were also given for study of entire frame system of a buildings and bridge structures under synergetic effects of combined blastimpact loads resulting partial or total progressive collapse.…”
Section: Response Of Structures Under Blastmentioning
confidence: 99%
“…The methods proposed in [77,78] were used in order to quantify and compare column removal scenario results from the aspect of the risk of progressive collapse of the structure. Damage limit states (LS) of the structure were determined for the results obtained using the NDA method.…”
Section: Damage Limit Statesmentioning
confidence: 99%
“…(redundancy) [7]. Structures designed in accordance with recommendations for seismically resistant buildings show lower fragility than those that are not designed in accordance with seismic regulations [77]. After a column is removed, a beam with a double span is formed, so that the lower and side reinforcement should be continued, which is necessary in seismically active areas.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Non-linear static analysis is helpful in evaluating the resilient and collapse failure limits of the system, even though it cannot account for the dynamic effect due to the sudden missing of columns studied by E.Brunesi, F.Parisi, etal. [7]. "Experimental studies [14], [17], [18]; carried out on RC beam-column sub assemblages have shown the inherent ability to better resist progressive collapse of the specimens with seismic detailing".…”
Section: Introductionmentioning
confidence: 99%